Conversations about Psychology. - Burton, Howard (Ideas Roadshow Collections., 2021)
Conversations About Psychology, Volume 1, is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading experts with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Diana Deutsch, Professor of Psychology at UC San Diego; 2. Chris Frith, Emeritus Professor of Neuropsychology at University College London; 3. Stephen Hinshaw, Professor.